Effect of Particulate Matter on Human Health, Prevention, and Imaging Using PET or SPECT - Javeria Zaheer; Jongho Jeon; 이승복; 김진수 (한국의학물리학회, 2018)
Particulate matter (PM) in dust causes serious pathological conditions, and it has been considered a critical health issue for many years. Respiratory disorders such as bronchitis, asthma, and chronic inflammation, are the most common illnesses due to PM that appears as dust. There is evidence that cardiovascular and neurological abnormalities are caused by PM. Although an extensive amount of work has been conducted on this topic, including studies on the nature of the particles, particle size measurements, particle distribution upon inhalation, the health effects of fine particles, disease prevention, diagnosis, and treatment, to this date, there is still a considerable lack of knowledge in these areas. Therefore, the identification of the key components that cause diseases owing to PM, and the specific diagnoses of the diseases, is important. This review will explore the current literature on the origin and nature of PM and their effects on human health. In addition, it will also highlight the approaches that have been adopted in order to diagnose the effects of PM using positron emission tomography (PET) or single-photon emission computerized tomography (SPECT).